Trends in Veterinary Sciences current aspects in Veterinary Morphophysiology, Biochemistry, Animal Production, Food Hygiene and Clinical Sciences - Ferlazzo, Adriana; Gaiti, Alberto; Pugliese, Antonio (Springer Berlin Heidelberg Imprint Springer, 2013)
Veterinary science is continuously achieving important developments in all its fields as a result of  continuous technological advances in diagnostic tools and applied biology. This book contains 33 papers that were selected from those presented at the 65th Congress of the Italian Society for Veterinary Sciences held at Tropea-Drapia in 2011. It provides a timely overview of the current progress being made by Italian researchers and is of great value to anyone interested in all fields of veterinary science, both theoretical and applied, ranging from animal health and care to animal production and food hygiene.